2013
DOI: 10.4038/gmj.v18i1.5522
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of myocardial ischaemia among diabetics determined by validated Sinhala version of the WHO Rose angina questionnaire

Abstract: Objectives:Design Setting: Results:Interpretation:The aim of this study was to validate the original version of the Rose Angina Questionnaire (RAQ) and apply it to a group of long standing diabetics in a cross-sectional manner to assess it applicability in clinical settings.After a face validation and piloting the Part A of the Sinhala translated RAQ (SRAQ-Part A) was given to 47 adult patients who presented with chest pain where the possibility of stable angina was considered in the differential diagnosis. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
(4 reference statements)
1
2
0
Order By: Relevance
“…Diabetes was noted among 10 (7%) individuals, while 25 (17%) had both diabetes and hypercholesterolemia, simultaneously. Though the statistical figure for diabetes (6%) is nearly consistent as compared with the study of Mendis S and Ekanayake E M in 1994 in Central Sri Lanka, [13] the prevalence of hypercholesterolemia among this hypertensive population was observed to be higher (12.6%) than previous findings.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Diabetes was noted among 10 (7%) individuals, while 25 (17%) had both diabetes and hypercholesterolemia, simultaneously. Though the statistical figure for diabetes (6%) is nearly consistent as compared with the study of Mendis S and Ekanayake E M in 1994 in Central Sri Lanka, [13] the prevalence of hypercholesterolemia among this hypertensive population was observed to be higher (12.6%) than previous findings.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, the definitive evidence of IHDs (positive symptoms and ECG changes of ischemia) was 16/1000 (95% CL, 9-27) followed by the evidence on ECG changes of ischemia without symptoms was 32/1000 (95% CL, 21-46). [13] As hypertension has been recognized as a prominent but modifiable risk factor for IHDs nevertheless due to the lack of advanced diagnostic methods in the most of local health care settings, the hypertensive patients who are still asymptomatic but at risk of IHDs probably miss the opportunity to undergo early screening and detection of potentially preventable myocardial ischemic changes. Further, they lack the opportunity to undergo detailed early screening methods like RAQ due to the rush in overcrowded clinics conducted at the hospitals in Sri Lanka.…”
Section: Introduction a N D B Ac Kg R O U N Dmentioning
confidence: 99%
“…The original version of the questionnaire was developed in 1962 to assess triggering and mitigating factors as well as the location, frequency, nature, severity, and duration of chest pain [24]. Compared to clinical diagnoses, exercise echocardiograms (ECGs), and myocardial perfusion scans, the questionnaire had a sensitivity of 53–86% and specificity of 70–89% [25,26].…”
Section: Methodsmentioning
confidence: 99%
“…In large-scale epidemiological surveys, the RAQ, which has a moderate sensitivity but high specificity to detect CHD, can be used to evaluate individual at risk [19]. The questionnaire showed a sensitivity of 53-86% and a specificity of 70-89% in comparison to clinical diagnoses, exercise echocardiograms (ECGs), and myocardial perfusion scans [19,20]. In addition to this, another study also reported varying sensitivity and specificity of the RAQ depending on the gold standard employed, but generally, there has been high specificity (80-95%) but variable sensitivity (19-83%) [21].…”
Section: Introductionmentioning
confidence: 99%